Implementasi Nilai-Nilai Dakwah, Budaya Dan Kearifan Lokal Dalam Sedekah Bumi - Moch. Hanna Wijaya Saputra; Luthfi Hidayah (An-Nashiha: Journal of Broadcasting and Islamic Comunication Studies, 2022)
This study aims to find out what are the implementations of da'wah values ​​and implementation in the earth alms tradition in Surowiti Village, Panceng District, Gresik Regency. This research uses the type of field research, primary sources in the form of observations by visiting the research location, in-depth interviews about Islamic cultural values ​​and local wisdom as well as the procession of the implementation of the earth alms tradition, and documentation of activities. The results of this study are about the values ​​of da'wah, culture and local wisdom which consist of the value of gratitude, the value of alms, the value of friendship, the value of worship, and the value of ukhuwah Islamiyah as well as the process of implementing the earth alms tradition.